A Biomimetic Self‐Shield Interface for Flexible Perovskite Solar Cells with Negligible Lead Leakage. (13th October 2021) - Meng, Xiangchuan; Hu, Xiaotian; Zhang, Yanyan; Huang, Zengqi; Xing, Zhi; Gong, Chenxiang; Rao, Li; Wang, Hongyu; Wang, Fuyi; Hu, Ting; Tan, Licheng; Song, Yanlin; et al.
Abstract: Although outstanding power conversion efficiency (PCE) has been achieved in flexible perovskite solar cells, unsatisfactory operational stability and toxicity caused by the moisture transmittance of polymer packaging are still the bottleneck challenges that limit their applications. Herein, inspired by the non‐selective permeability of inactivated cell membrane, the diphosphatidyl‐glycerol (Di‐g) is tactfully introduced as a self‐shield interface upon the perovskite layer. 96% of lead leakage is suppressed because the amphipathic Di‐g can simultaneously bind tightly to the divalent lead ion and afford an interfacial water‐resistance. More importantly, the gradient distribution of lattice residual stress perpendicular to the substrate are optimized. The resultant flexible devices achieve a PCE of 20.29% and 15.01% at effective areas of 1.01 and 21.82 cm 2 respectively, yielding excellent environmental and mechanical stability. This strategy exhibits the feasibility of developing interfacial encapsulation to stabilize scalable PSCs with negligible lead leakage. Abstract : Stability and toxicity of PSCs are bottleneck challenges for their commercial development. Herein, biomimetic Di‐g molecules are introduced to the encapsulated FPSCs as the interface layer, which improves the efficiency of 1.01 cm 2 FPSCs up to 20.29%. Importantly, they demonstrate excellent mechanical stability and lead leakage suppression, the efficiency maintains 85% of initial value without ion leakage under 10 000 bending cycles.